A gradient based model for the mesh-independent damage simulation of layered composite structures. (September 2019) - Läufer, J.; Wagner, W.
Highlights: New damage model for composite material. Gradient based formulation leads to a non-local model. Based on the non-local model: no FE-mesh dependency. New extension to a multi-layer formulation. Embedding in a nonlinear shell formulation. Abstract: Over the last decades, fiber composite materials have established themselves especially for problems in lightweight construction. In order to use the structure optimally, a precise knowledge of the maximum load-bearing capacity and possible damage to the structure is necessary. For the calculation of damage in fiber composite laminates, various damage models already exist. Classically, these models are applied within the finite element method (FEM). Localization effects occur which lead to a dependence of the results on the used FE-mesh. This paper deals with the gradient extension of free Helmholtz energy using global damage variables to eliminate localization effects. Based on the formulation of the regularized damage model of the single layer, the regularization is transformed into a layered theory for composite shell structures. The associated numerical model within the framework of FEM is explained before the model is illustrated with numerical examples.